George Hunt : Arizona's Crusading Seven-Term Governor - Berman, David R. (Book collections on Project MUSE., 2015)
"This is a political biography of Arizona's first elected (state) governor, George W.P. Hunt. It follows Hunt closely through his years in the Territorial legislature and then as governor and minister to Siam. The author assesses Hunt's successes and failings as a political leader"--Provided by publisher